Comparison of Quality of Life between Working Mothers and Housewives - Irham; Delfia Herwanis Wahid (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The conversation about working women and housewives is still a debate that is often found in various moments, whether it is on social media or in real life. This research is a library research, which aims to reveal some research results on the views of working women and non-working women in terms of quality of life by using descriptive qualitative methods, research data taken from 2015-2020 totaling ten research results. These ten studies are the primary data used in this article. From the data it can be concluded that the quality of life of non-working women gets twice the positive response compared to the quality of life of working women, although in a small part of the quality of life of working women gets a positive response.